The art as a tool of counselling process in the activity of social workers and psychologists - Anna Ivashchenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article is devoted to the relevance of using art as a tool of counseling. Psychological approaches to understanding art, product of creativity and the creative process are identified. The features of using client-centered therapy based on expressive arts are described. Example of the work with art in dealing with group dynamics is presented in the article.